Effect of Lubricants on the Lubricity of an Intervention Base Oil (Annual Transactions of the Nordic Rheology Society, 2024)
During well intervention operations, the production tubing wall could be worn out due to  mechanical interaction with coil tubing. Wear damage is a critical issue in the bend section  where the contact force is higher. One of the possible solutions to reduce friction and wear  damage is by increasing the lubricity of the intervention and the drilling fluid as well. The  improved lubricity also minimizes the torque and drag that allows for reaching longer offset.  This paper presents the experimental studies of the impact of six lubricants on industry  intervention fluid. Results showed that the lubricants enhance the lubricity of the base oil. The  optimized concentration of the lubricant reduced the coefficient of friction by 42-72 %.